Magnetic nanoparticles and application thereof in preparation of caprolactone from cyclohexanone
By using Fe3O4-P@SiO2 magnetic nanoparticles as catalysts, the problem of harsh reaction conditions and difficult catalyst recovery in the traditional cyclohexanone preparation method is solved, and efficient catalytic reaction under mild conditions is achieved, and the recovery rate and stability of the catalyst are improved.
Patent Information
- Application Number
- CN202411576675.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-06
- Publication Date
- 2025-03-14
AI Technical Summary
The traditional method of preparing caprolactone in cyclohexanone has the safety hazards of harsh reaction conditions, high concentration peroxyacid volume explosion, and the difficulty in recycling and reusing of catalysts.
Fe3O4-P@SiO2 magnetic nanoparticles are used as catalysts. The nanoparticles have high activity and good magnetic properties, and can be quickly separated and recovered under the action of an external magnetic field.
This catalyst can effectively catalyze the preparation of caprolactone under mild conditions, reduce the reaction temperature, avoid the hydrolysis of caprolactone, improve the conversion and selectivity of the reaction, and the catalyst is easy to recover and reuse, and has good stability.
Smart Images

Figure CN119608191A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of catalysts and chemical synthesis, and in particular to magnetic nanoparticles and application thereof in preparing caprolactone from cyclohexanone. Background Art
[0002] Magnetic nanoparticles have a wide range of applications in the field of catalytic materials and chemical synthesis due to their unique physical and chemical properties. The advantages of magnetic nanoparticles include high specific surface area, good biocompatibility, easy functionalization, and the ability to be separated and controlled by an external magnetic field. In the field of catalytic materials, magnetic nanocatalysts have become a hot topic of research due to their easy recycling and reuse.
[0003] Polycaprolactone is a homopolymer of 2-oxacycloheptanone, which is a white solid powder and a synthetic polymer. It has a variety of excellent physical and chemical properties and biocompatibility, can be safely degraded in the human body, and has good biodegradability. Therefore, it can be used to manufacture a variety of materials, such as medical sutures, drug sustained-release agents, coated stents, antibacterial materials, etc. Caprolactone is the main raw material for the preparation of polycaprolactone. Caprolactone is mainly prepared from cyclohexanone. The traditional preparation method is mainly the indirect oxidation method with hydrogen peroxide. Since the reaction is a strong oxidative exothermic reaction, there are many safety hazards. At present, only UCC, Daicel, Ingevity, BASF, and Hunan Juren in China can produce it. The reaction process usually uses a homogeneous acid catalyst to speed up the reaction and reduce by-products, but there are problems such as harsh reaction conditions, high concentration of peroxy acid, high safety hazards of explosion, and difficulty in recycling the catalyst. Therefore, it is urgent to develop a heterogeneous catalyst so that the reaction can be carried out under milder conditions, and the catalyst can be quickly separated and recycled to improve the yield of the reaction. Summary of the invention
[0004] The present invention provides a magnetic nanoparticle and its application in preparing caprolactone from cyclohexanone; the nanoparticle has both strong paramagnetic property and high activity, and the preparation method is simple. After the reaction is completed, it can be quickly enriched, recovered and reused under the action of an external magnetic field.
[0005] The technical solution of the present invention is to provide a magnetic nanoparticle, which is Fe 3 O 4 -P@SiO 2 The core-shell structure is prepared by mixing iron salt and organic acid salt as raw materials in an alcohol solution and then hydrothermally crystallizing to prepare Fe 3 O 4 Magnetic nanopowder; then Fe 3 O 4 Magnetic nanopowders were treated with phosphate solution to obtain Fe 3 O4 -P magnetic nanopowder; finally, Fe 3 O 4 -P magnetic nanopowder is dispersed in an alcohol solution, and ammonia and siloxane are added to react. After separation, drying and calcination, Fe 3 O 4 -P@SiO 2 Magnetic nanoparticles.
[0006] In an alternative embodiment, Fe 3 O 4 The preparation of magnetic nanopowders meets at least one of the following conditions: 1) The iron salt is one or more of nitrate, chloride, and ferric sulfate; 2) The organic acid salt is one or more of sodium citrate, sodium malate, and sodium acetate; 3) The mass ratio of the iron salt to the organic acid salt is 1-3:2-10; 3) The alcohol solution is a dihydric or trihydric alcohol with two to five carbon chains.
[0007] In an optional scheme, the temperature of the hydrothermal crystallization is 160-220°C and the time is 8-12h; after the hydrothermal crystallization is completed, Fe is separated and washed to obtain 3 O 4 Magnetic nanopowder.
[0008] In an alternative embodiment, Fe 3 O 4 -P magnetic nanopowders meet at least one of the following conditions during preparation: the phosphate is one or a combination of ammonium phosphate, monoammonium hydrogen phosphate, and diammonium hydrogen phosphate; and the mass concentration of the phosphate is 3%-30%.
[0009] In an alternative embodiment, Fe 3 O 4 The magnetic nanopowder was added to the phosphate solution and then ultrasonically treated, and then allowed to stand, filtered, washed, dried and calcined to obtain Fe 3 O 4 -P magnetic nanopowder.
[0010] In an optional solution, the calcination temperature is 400-550°C.
[0011] In an alternative embodiment, Fe 3 O 4 -P@SiO 2 The magnetic nanoparticles are prepared by satisfying at least one of the following conditions: 1) The alcohol solution is a dihydric or trihydric alcohol with two to five carbon chains, preferably ethylene glycol, glycerol and / or 1,2-propylene glycol; 2) Ammonia concentration is 5~15mol / L; 3) Siloxane is one or a combination of benzene-containing lower siloxanes; it may be phenyltrimethoxysilane, phenyltriethoxysilane, methylphenyldiethoxysilane and / or diphenyldihydroxysilane; 4) The mass ratio of siloxane to ammonia water is 3~8:5.
[0012] In an alternative embodiment, Fe 3 O 4 -P@SiO 2 The calcination temperature of the magnetic nanoparticles after drying is 500-600°C.
[0013] The invention also relates to the use of the magnetic nanoparticles as a catalyst when preparing caprolactone by using cyclohexanone.
[0014] In a further application, when cyclohexanone is used to prepare caprolactone, hydrogen peroxide is used as an oxidant and the oxidation temperature is 20-50°C.
[0015] The present invention has the following beneficial effects: The present invention uses Fe 3 O 4 Nanomaterials are used as cores, and the surface is modified by phosphating to increase polarizability and show extremely high electron-deficient electrophilic activity. 2 Package, obtained Fe 3 O 4 -P@SiO 2 Magnetic nanoparticles have a simple preparation process, readily available raw materials, good magnetic properties and high crystallinity. They exhibit excellent catalytic performance and extremely high selectivity in the preparation of caprolactone from cyclohexanone, can reduce the reaction temperature, and can avoid the hydrolysis of caprolactone, further improving the reaction conversion rate and selectivity. The catalyst is easy to separate, has a high recovery rate, can be recycled, and has good stability. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] Figure 1 The Fe obtained in Example 1 3 O 4 -P@SiO 2 SEM image of magnetic nanoparticles. DETAILED DESCRIPTION
[0017] The present invention is described in detail below in conjunction with specific embodiments. This embodiment is implemented based on the technical solution of the present invention, and provides a detailed implementation method and a specific operation process, but the protection scope of the present invention is not limited to the following embodiments.
[0018] The experimental methods in the following examples are conventional methods unless otherwise specified. The raw materials, reagents, etc. used in the following examples are commercially available products unless otherwise specified.
[0019] Example 1 (1) Fe 3 O 4 -P@SiO 2 Preparation of magnetic nanoparticles: 2.6 g of ferric chloride hexahydrate and 3.3 g of sodium citrate were dissolved in 60 mL of ethylene glycol and stirred magnetically to obtain a yellow solution. The solution was then transferred to a 100 ml stainless steel autoclave with a polytetrafluoroethylene liner and heated at 180 ° C for 12 h. After cooling to room temperature, the magnetic nanoparticles were separated and collected by a magnet. The particles were washed with deionized water and ethanol for 4 times and dried at 60 ° C for 12 h to obtain Fe 3 O 4 Magnetic nanoparticles.
[0020] Take 1g of Fe 3 O 4 The magnetic nanoparticles were dispersed in 20 ml of 10% ammonium phosphate aqueous solution, ultrasonicated for 30 min, then immersed for 12 h, separated and collected by magnet, dried at 120 °C for 6 h, and then calcined in a muffle furnace at 450 °C for 5 h to obtain Fe 3 O 4 -P magnetic nanoparticles.
[0021] Take 1g of Fe 3 O 4 -P magnetic nanoparticles were dispersed in 80 ml of ethanol, ultrasonicated for 10 min, and then 3 ml of 10 mol / L ammonia solution and 4.5 g of phenyltrimethoxysilane were added in sequence, stirred at 35 ° C for 8 h for hydrolysis, polymerization, and magnetic nanoparticles were collected by magnetic separation, and then washed with deionized water and ethanol for 3 times, vacuum dried at 60 ° C for 6 h, and then calcined at 550 ° C for 4 h to obtain Fe 3 O 4 -P@SiO 2 Core-shell structured magnetic nanoparticles.
[0022] (2) Preparation of caprolactone from cyclohexanone: Weigh 0.2g of the Fe prepared above 3 O 4 -P@SiO 2Magnetic nanoparticles were used as catalysts, 12.3 g of propionic acid, 1 drop of 2-methylpyridine, and 18 g of cyclohexane with water were added to a three-hole flask, 7 g of 50% hydrogen peroxide was weighed and added to a constant pressure dropping funnel, the mixture was evacuated to 500 mHg, the temperature was raised to 50°C, and hydrogen peroxide was added dropwise at a stirring speed of 500 rpm. After the addition was completed, the dehydration reaction was continued for 2 h. After the addition was completed, the vacuum device was removed, the temperature was lowered to 40°C, and 2.7 g of cyclohexanone was continued to be added dropwise. After the addition was completed, the reaction was continued for 1 h. The temperature was lowered and the stirring was stopped. The catalyst was separated by a magnet, and the product was subjected to gas phase detection and analysis.
[0023] Embodiment 2: (1) Fe 3 O 4 -P@SiO 2 Preparation of magnetic nanoparticles: 2.6 g of ferric chloride hexahydrate and 4.0 g of sodium malate were dissolved in 60 mL of ethylene glycol and stirred magnetically to obtain a yellow solution. The solution was then transferred to a 100 ml stainless steel autoclave with a polytetrafluoroethylene liner and heated at 210 °C for 12 h. The magnetic nanoparticles were collected by magnetic separation and washed with deionized water and ethanol for 4 times and dried at 60 °C for 12 h to obtain Fe 3 O 4 Magnetic nanoparticles.
[0024] Take 1g of Fe 3 O 4 The magnetic nanoparticles were dispersed in 20 ml of 10% ammonium phosphate aqueous solution, ultrasonicated for 30 min, then immersed for 12 h, separated and collected by magnet, dried at 120 °C for 6 h, and then calcined in a muffle furnace at 450 °C for 5 h to obtain Fe 3 O 4 -P magnetic nanoparticles.
[0025] Take 1g of Fe 3 O 4 -P magnetic nanoparticles were dispersed in 80 ml of ethanol, ultrasonicated for 10 min, and then 3 ml of 10 mol / L ammonia solution and 4.5 g of phenyltrimethoxysilane were added in sequence, stirred at 35 ° C for 8 h for hydrolysis, polymerization, and magnetic nanoparticles were collected by magnetic separation, and then washed with deionized water and ethanol for 3 times, vacuum dried at 60 ° C for 6 h, and then calcined at 550 ° C for 4 h to obtain Fe 3 O 4 -P@SiO 2 Core-shell structured magnetic nanoparticles.
[0026] The preparation of caprolactone from cyclohexanone is the same as in Example 1, and the catalyst is the catalyst of this example.
[0027] Embodiment 3: (1) Fe 3 O 4 -P@SiO 2 Preparation of magnetic nanoparticles: 2.6 g of ferric chloride hexahydrate and 3.3 g of sodium citrate were dissolved in 60 mL of propylene glycol and stirred magnetically to obtain a yellow solution. The solution was then transferred to a 100 ml stainless steel autoclave with a polytetrafluoroethylene liner and heated at 180 ° C for 12 h. The magnetic nanoparticles were collected by magnetic separation, washed with deionized water and ethanol for 4 times, and dried at 60 ° C for 12 h to obtain Fe 3 O 4 Magnetic nanoparticles.
[0028] Take 1g of Fe 3 O 4 The magnetic nanoparticles were dispersed in 20 ml of 10% diammonium phosphate aqueous solution, ultrasonicated for 30 min, then immersed for 12 h, separated and collected by magnet, dried at 120 °C for 6 h, and then calcined in a muffle furnace at 450 °C for 5 h to obtain Fe 3 O 4 -P magnetic nanoparticles.
[0029] Take 1g of Fe 3 O 4 -P magnetic nanoparticles were dispersed in 80 ml of ethanol, ultrasonicated for 10 min, and then 3 ml of 10 mol / L ammonia solution and 4.5 g of phenyltrimethoxysilane were added in sequence, stirred at 35 ° C for 8 h for hydrolysis, polymerization, and magnetic nanoparticles were collected by magnetic separation, and then washed with deionized water and ethanol for 3 times, vacuum dried at 60 ° C for 6 h, and then calcined at 550 ° C for 4 h to obtain Fe 3 O 4 -P@SiO 2 Core-shell structured magnetic nanoparticles.
[0030] (2) Preparation of caprolactone from cyclohexanone The same method as in Example 1 was used, except that the catalyst was the catalyst of this example.
[0031] Embodiment 4: (1) Fe 3 O 4 -P@SiO 2 Preparation of magnetic nanoparticles: 2.6 g of ferric chloride hexahydrate and 3.3 g of sodium citrate were dissolved in 60 mL of propylene glycol and stirred magnetically to obtain a yellow solution. The solution was then transferred to a 100 ml stainless steel autoclave with a polytetrafluoroethylene liner and heated at 180 ° C for 12 h. The magnetic nanoparticles were collected by magnetic separation, washed with deionized water and ethanol for 4 times, and dried at 60 ° C for 12 h to obtain Fe 3 O 4Magnetic nanoparticles.
[0032] Take 1g of Fe 3 O 4 The magnetic nanoparticles were dispersed in 20 ml of 10% ammonium phosphate aqueous solution, ultrasonicated for 30 min, then immersed for 12 h, separated and collected by magnet, dried at 120 °C for 6 h, and then calcined in a muffle furnace at 450 °C for 5 h to obtain Fe 3 O 4 -P magnetic nanoparticles.
[0033] Take 1g of Fe 3 O 4 -P magnetic nanoparticles were dispersed in 80 ml of ethanol, ultrasonicated for 10 min, and then 3 ml of 10 mol / L ammonia solution and 4.5 g of phenyltriethoxysilane were added in sequence, stirred at 35 ° C for 8 h for hydrolysis, polymerization, and magnetic nanoparticles were collected by magnetic separation, and then washed with deionized water and ethanol for 3 times, vacuum dried at 60 ° C for 6 h, and then calcined at 550 ° C for 4 h to obtain Fe 3 O 4 -P@SiO 2 Core-shell structured magnetic nanoparticles.
[0034] (2) Preparation of caprolactone from cyclohexanone: Same as Example 1, except that the catalyst is the catalyst of this example.
[0035] Example 5 Compared with Example 1, the only difference is that the iron salt is ferric nitrate nonahydrate and the amount used is 3.9 g.
[0036] Example 6 Compared with Example 1, the only difference is that the iron salt is ammonium ferric sulfate dodecahydrate, and the amount used is 4.6 g.
[0037] Example 7 Compared with Example 1, the only difference is that the organic acid salt is sodium malate and the amount used is 3.7 g.
[0038] Example 8 Compared with Example 1, the only difference is that the organic acid salt is sodium acetate and the amount used is 3.7 g.
[0039] Example 9 Compared with Example 1, the only difference is that the hydrothermal crystallization temperature of the magnetic nanoparticles is 210° C. and the time is 8 hours.
[0040] Example 10 Compared with Example 1, the only difference is that the phosphate is ammonium dihydrogen phosphate, and its mass concentration is 25%.
[0041] Embodiment 11 Compared with Example 1, the only difference is that Fe 3 O 4 The calcination temperature of magnetic nanoparticles is 500℃, Fe 3 O 4 -P@SiO 2 The calcination temperature of the magnetic nanoparticles is 500°C.
[0042] Example 12 Compared with Example 1, the only difference is that the concentration of ammonia water is 15 mol / L.
[0043] Embodiment 13 Compared with Example 1, the only difference is that the reaction temperature is 30°C when the cyclohexanone oxidation reaction is carried out.
[0044] The implementation effects of the above embodiments 1-13 are shown in Table 1 below.
[0045] Table 1
[0046] Comparative Example 1: (1) Fe 3 O 4 @SiO 2 Preparation of magnetic nanoparticles: Dissolve 2.6 g of ferric chloride hexahydrate and 3.3 g of sodium citrate in 60 mL of ethylene glycol and stir magnetically to obtain a yellow solution. Then transfer the solution to a 100 ml stainless steel autoclave with a polytetrafluoroethylene liner, heat at 180 ° C for 12 h, cool to room temperature, separate and collect magnetic nanoparticles with a magnet, wash with deionized water and ethanol for 4 times, and dry at 60 ° C for 12 h to obtain Fe3O4 magnetic nanoparticles.
[0047] Take 1g of Fe 3 O 4 The magnetic nanoparticles were dispersed in 80 ml of ethanol and ultrasonicated for 10 min. Then, 3 ml of 10 mol / L ammonia solution and 4.5 g of phenyltriethoxysilane were added in sequence. The mixture was stirred at 35 °C for 8 h for hydrolysis and polymerization. The magnetic nanoparticles were collected by magnetic separation. The particles were then washed with deionized water and ethanol for 3 times, vacuum dried at 60 °C for 6 h, and then calcined at 550 °C for 4 h to obtain Fe 3 O 4 @SiO 2 Core-shell structured magnetic nanoparticles.
[0048] (2) Preparation of caprolactone from cyclohexanone: The same as in Example 1, except that the catalyst was prepared in Comparative Example 1. The cyclohexanone conversion rate was 99.2%, and the caprolactone selectivity was 30.7%. After the catalyst was recycled for 6 times, the conversion rate was 91.2% and the selectivity was 11.2%.
[0049] It can be seen from Comparative Example 1 that Fe without P modification 3 O 4 @SiO 2 Magnetic nanoparticles are used in the oxidation reaction of cyclohexanone, but the selectivity of caprolactone is low, and after multiple cycles, the selectivity decreases significantly, resulting in poor catalytic performance.
[0050] Comparative Example 2: (1) Fe 3 O 4 -P@SiO 2 Preparation of magnetic nanoparticles: 2.6 g of ferric chloride hexahydrate and 3.3 g of sodium citrate were dissolved in 60 mL of ethylene glycol and stirred magnetically to obtain a yellow solution. The solution was then transferred to a 100 ml stainless steel autoclave with a polytetrafluoroethylene liner and heated at 180 ° C for 12 h. After cooling to room temperature, the magnetic nanoparticles were separated and collected by a magnet. The particles were washed with deionized water and ethanol for 4 times and dried at 60 ° C for 12 h to obtain Fe 3 O 4 Magnetic nanoparticles.
[0051] Take 1g of Fe3O4 magnetic nanoparticles, disperse them in 20ml of 10% ammonium phosphate aqueous solution, ultrasonicate for 30min, then immerse for 12h, separate and collect the magnetic nanoparticles with a magnet, dry them at 120℃ for 6h, and then calcine them at 450℃ in a muffle furnace for 5h to obtain Fe 3 O 4 -P magnetic nanoparticles.
[0052] Take 1g of Fe 3 O 4 -P magnetic nanoparticles were dispersed in 80 ml of ethanol, ultrasonicated for 10 min, and then 3 ml of 10 mol / L ammonia solution and 4.5 g of tetramethoxysiloxane were added in sequence, stirred at 35 ° C for 8 h for hydrolysis, polymerization, and magnetic nanoparticles were collected by magnetic separation, and then washed with deionized water and ethanol for 3 times, vacuum dried at 60 ° C for 6 h, and then calcined at 550 ° C for 4 h to obtain Fe 3 O 4 -P@SiO 2 Core-shell structured magnetic nanoparticles.
[0053] (2) Preparation of caprolactone from cyclohexanone: The same as in Example 1, except that the catalyst was prepared in Comparative Example 1. The cyclohexanone conversion was 21.0%, and the caprolactone selectivity was 19.2%. After the catalyst was recycled for 6 times, the conversion was 11.3% and the selectivity was 15.4%.
[0054] Comparison between Example 1 and Comparative Example 2 shows that the Fe 3 O4 -P@SiO 2 The catalytic performance of magnetic nanoparticles is poor, the conversion rate of cyclohexanone and the selectivity of caprolactone are both low, and after repeated use, the conversion rate and catalytic performance both decrease.
[0055] The above embodiments describe the preferred implementation of the present invention, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A magnetic nanoparticle, characterized in that: It is a Fe3O4-P@SiO2 core-shell structure. Specifically, during preparation, iron salt and organic acid salt are first used as raw materials, mixed in an alcohol solution, and hydrothermally crystallized to prepare Fe3O4 magnetic nanopowder; then the Fe3O4 magnetic nanopowder is added to a phosphate solution for treatment to obtain Fe3O4-P magnetic nanopowder; finally, the Fe3O4-P magnetic nanopowder is dispersed in an alcohol solution, ammonia water and siloxane are added to react, and Fe3O4-P@SiO2 magnetic nanoparticles are obtained after separation, drying and calcination.
2. The magnetic nanoparticles according to claim 1, characterized in that The preparation of Fe3O4 magnetic nanopowder meets at least one of the following conditions: 1) The iron salt is one or more of nitrate, chloride and sulfate; 2) The organic acid salt is one or more of sodium citrate, sodium malate, and sodium acetate; 3) The mass ratio of the iron salt to the organic acid salt is 1-3:2-10; 3) The alcohol solution is a dihydric or trihydric alcohol with two to five carbon chains.
3. The magnetic nanoparticle according to claim 1, characterized in that: The temperature of the hydrothermal crystallization is 160-220° C., and the time is 8-12 hours. After the hydrothermal crystallization is completed, Fe3O4 magnetic nanopowder is obtained through separation, washing and drying.
4. The magnetic nanoparticles according to claim 1, characterized in that The preparation of Fe3O4-P magnetic nanopowder satisfies at least one of the following conditions: the phosphate is one or a combination of ammonium phosphate, monoammonium hydrogen phosphate, and diammonium hydrogen phosphate; and the mass concentration of the phosphate is 3%-30%.
5. The magnetic nanoparticle according to claim 1, characterized in that: Fe3O4 magnetic nanopowder is added into phosphate solution and then ultrasonically treated, and then allowed to stand, filtered, washed, dried and calcined to obtain Fe3O4-P magnetic nanopowder.
6. The magnetic nanoparticle according to claim 5, characterized in that: The calcination temperature is 400-550℃.
7. The magnetic nanoparticle according to any one of claims 1 to 6, characterized in that: The preparation of Fe3O4-P@SiO2 magnetic nanoparticles meets at least one of the following conditions: 1) The alcohol solution is a dihydric or trihydric alcohol with two to five carbon chains; 2) Ammonia concentration is 5~15mol / L; 3) Siloxane is one or a combination of benzene-containing lower siloxanes; 4) The mass ratio of siloxane to ammonia water is 3~8:
5.
8. The magnetic nanoparticle according to claim 1, characterized in that: The calcination temperature of the Fe3O4-P@SiO2 magnetic nanoparticles after drying is 500-600°C.
9. Use of the magnetic nanoparticles according to any one of claims 1 to 8 as a catalyst in the preparation of caprolactone from cyclohexanone.
10. The use according to claim 9, characterized in that: When cyclohexanone is used to prepare caprolactone, hydrogen peroxide is used as the oxidant and the oxidation temperature is 20~50℃.